2023
DOI: 10.51847/vyxpgt2lgb
|View full text |Cite
|
Sign up to set email alerts
|

Use and Success Rate of Lasers in the Treatment of Gingival Melanin Pigmentation: A Systematic Review

Abstract: The pigmentation of oral soft tissues is predominantly an aesthetic problem because lifestyle, media, and social influences impact people's perception of beauty, which in turn affects their self-esteem as well as their relationships. The melanin pigmentation of the gingiva has become a real concern in the Gulf region, especially for younger people and females, who seek aesthetic solutions to remove the pigmentation. The pigmentation caused by melanin can be removed by surgical blades, diamond burs, chemicals, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Another systematic review was conducted to assess the effect of two distinct laser types: the Diode and Erbium on the treatment of melanin pigmentation in terms of their ability to remove discoloration, pain, bleeding, longevity, and overall patient experience. The findings indicated that diode laser was significantly more effective as compared to Erbium lasers (22). Alasbahi et al compared between the effectiveness of Nd:YAG laser and Diode laser in managing physiologic gingival melanin pigmentation, and concluded that both laser types were effective without any significant difference observed between them (18).…”
Section: Discussionmentioning
confidence: 99%
“…Another systematic review was conducted to assess the effect of two distinct laser types: the Diode and Erbium on the treatment of melanin pigmentation in terms of their ability to remove discoloration, pain, bleeding, longevity, and overall patient experience. The findings indicated that diode laser was significantly more effective as compared to Erbium lasers (22). Alasbahi et al compared between the effectiveness of Nd:YAG laser and Diode laser in managing physiologic gingival melanin pigmentation, and concluded that both laser types were effective without any significant difference observed between them (18).…”
Section: Discussionmentioning
confidence: 99%